PENGARUH PROFESIONALISME DAN INDEPENDENSI TERHADAP KINERJA AUDITOR INTERNAL PEMERINTAH DIMEDIASI OLEH PEMAHAMAN TERHADAP GOOD GOVERNANCE: (Studi Pada Inspektorat Provinsi Riau) - Sri Wahyuni Zanra; Yayu Kusdiana (CV. Denasya Smart Publisher, 2024)
This study aims to determine the effect of professionalism and independence on the performance of government internal auditors mediated by an understanding of good governance at the Riau Provincial Inspectorate. The research method used is quantitative research. The population in this study were all internal auditors at the Riau Provincial Inspectorate totaling 52 people. The data collection technique used was a structured questionnaire. The instrument testing technique in this study was the validity and reliability test using PLS (Partial Least Square) as its measurement. The results of this study indicate that professionalism and independence have a significant direct effect on the performance of internal auditors at the Riau Provincial Inspectorate. Likewise, an understanding of Good Governance is able to mediate the relationship between professionalism and independence and the performance of internal auditors at the Riau Provincial Inspectorate